In Pursuit of Sustainable Cultural Tourism Local and International Tourists Responses to Cultural Tourism Activities in Luang Prabang District, Lao PDR - SENGCHANH, Souksamone; INDAVONG, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
Cultural tourism has the potential to attract both international and domestic travelers. Its wealth of cultural resources. Ranging from its language, arts, festivals, folklore, handicraft, food, music, and way of life. The diversification of cultural activities is created by many stakeholders, such as the government, business owners, tourists, and also the local people who have been remarkable to attract tourists. We need to maintain, conserve and preserve the resources and assets in Luang Prabang. Based on “authenticity” and “uniqueness” which not only stands for culture itself but it is connected to the natural, historical culture of its people to make cultural tourism be more sustain. Using the concept of UNESCO, cultural tourism in Luang Prabang should focus more on protection, preservation and more restoration by local people themselves.